До питання корекції компонентів фізичного стану осіб зрілого віку в процесі занять профілактично-оздоровчої спрямованості - Кашуба, Віталій Олександрович; Футорний, Сергій Михайлович; Kashuba, Vitaliy; Futornyi, Sergey (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті вивчаються актуальні питання значимості й систем організації рухової активності чоловіків зрілого віку. Відповідно до аналізу даних сучасної літератури та моніторингу Інтернет-ресурсів установлено, що на сьогодні серед популярних видів рухової активності чоловіків зрілого віку є біг, ходьба, скандинавська ходьба й плавання оздоровчої спрямованості. Вивчення вітчизняних і міжнародних наукових розробок із цього питання дало змогу представити коротку характеристику результатів досліджень, навести статистичні дані та сформулювати практичні рекомендації. Modern perceptions and views for mature age men motor activity. The article is devoted to studying the means and organization systems of motor activity among men of mature age. According to the analysis data of modern literature and monitoring of Internet resources it was found that today the most popular kinds of motor activity among men of mature age are running, walking, Nordic walking and swimming improving orientation. Objectives of research: analysis of the data scientific and methodical literature concerning the issues of priority kinds of motor activity for men of mature age; generalize the domestic and world experience relative actuality question of chosen the kind of motor activity for men of mature age, as a leading factor in the direction of the formation not only of their own healthy lifestyle, and overall health. The study of national and international scientific research on the subject allowed submitting brief description results of research, statistical data and provided practical recommendations. Target orientation and its relevance in the implementation of chosen the kind of motor activity for men of mature age should include a range of awareness, understanding, willingness and desire to increase the level of their own health, its preservation and strengthening.
To Question for Correction of Components of Physical Condition of Mature Age Men in the Training Process of Recreational and Prevention of Directionality
Keywords: чоловіки зрілого віку; рухова активність; біг; ходьба; скандинавська ходьба; оздоровче плавання; здоров’я; men of mature age; physical activity; running; walking; Nordic walking; recreational swimming; health